Deradicalization programs in Indonesia: Bibliometric analysis of international publication trends from 1980 to 2022 - Gonda Yumitro; Rizki Febriani; Ali Roziqin; Nurdiana Abiyogha (Communications in Humanities and Social Sciences, 2022)
This study discusses about deradicalization in Indonesia with a bibliometric approach. The data presented in this study used the Scopus database and were visualized using the VOSviewer. The data collected were obtained by searching with the keywords "(TITLE-ABS-KEY (deradicalization) OR TITLE-ABS-KEY (deradicalisation) OR TITLE-ABS-KEY (counter-terrorism") AND TITLE-ABS-KEY (Indonesia)". This study aims to determine: (1) the number of documents; (2) the number of documents by the author; (3) the number of documents by affiliation; (4) the number of documents by country; (5) documents based on the subject area, (6) documentation based on the type of research, (7) co-occurrence and (8) co-author. The results of this study indicated that there were 262 documents discussing deradicalization in Indonesia from 1980 to 2022. The Islamic University of Indonesia became the most dominating university in writing articles on deradicalization and efforts to prevent the acts of terrorism. This showed that scholars actively study the theorizing and deradicalization issues in Indonesia. The highest publication was found in 2021 with 38 documents. Gunaratna, R became the author who has mostly discussed the deradicalization program in Indonesia with six documents. Most authors published articles; 68.7% of them do so, and 48.4% do so in the study of social science and political science.